PERAN PERPUSTAKAAN SEKOLAH DALAM MEMPROMOSIKAN BUDAYA BACA DI SMA SEBAGAI STRATEGI PENINGKATAN LITERASI SISWA - Lailatur Rahmi; Elviana (Universitas Terbuka, 2022)
The purpose of this study is to explain the role of school libraries in improving information literacy and reading culture of adolescents in high schools by choosing SMA N 16 Padang as the object of research and grade 3 as the research sample. The research method is descriptive quantitative by using questionnaires as a data collection tool using random sampling techniques. The results of the study were interpreted using simple percentages and arranged in a graph, with the results that students did not have good reading habits. Data shows that 45% of students spend only 30 minutes- 1 hour per day reading, focusing only on reading textbooks and school notes while doing homework and reading only for exams. The results also show that 60% of students very rarely borrow books in the library, and the library collection has not been integrated with the school curriculum beyond the thematic compulsory books available.